If the mean of a b c is M and ab…

Are you looking for correct answer of If the mean of a b c is M and ab…? Here we have shared detailed answer with explanations.

If the mean of a, b, c, is M and ab + bc + ca = 0, then the mean of a2, b2, c2 is –

  1. A. M2
  2. B. 3M2
  3. C. 6M2
  4. D. 9M2

Answer: Option B

Here is complete explanation of If the mean of a b c is M and ab….

Solution(By ExamCraze Team)

We have :
$$frac{a + b + c}{3}$$   = M
or (a + b + c) = 3M
Now, (a + b + c)2 = (3M)2 = 9M2
⇔ a2 + b2 + c2 + 2 (ab + bc + ca) = 9M2
⇔ a2 + b2 + c2 = 9M2
[$$because $$ (ab + bc + ca) = 0]
∴ Required mean
$$eqalign{ & = left( {frac{{{a^2} + {b^2} + {c^2}}}{3}} right) cr & = frac{{9{M^2}}}{3} cr & = 3{M^2} cr} $$

Leave a Comment